2012
DOI: 10.15835/nsb416660
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic and Inorganic Fertilizers on Nematode Reproduction and Biochemical Alterations on Tomato

Abstract: The organic amendments, compost, neem and poultry as well as inorganic fertilizer, N P K and nematicide Nemacur 10% G applied singly at two different doses were effective in reducing M. incognita number of galls, nematode reproduction and fecundity. Also, they ameliorated growth criteria of treated tomato plants. The effectiveness seemed to be material origin and concentration dependent. Neem, compost 1, 3 at higher doses (5 g/pot) gave the best results. Yet, achieved results were less than those of nemacur 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…Among the treatments, MOLE showed the most pronounced effect, while somewhat comparable effects were shown by the 6-BAP and the mixture treatments. A decrease in proline contents in comparison with the controls was reported earlier by Farahat et al (2012) during an investigation of exogenous applications of humic acid on seedlings of Khaya senegalensis.…”
Section: Proline Contentssupporting
confidence: 74%
“…Among the treatments, MOLE showed the most pronounced effect, while somewhat comparable effects were shown by the 6-BAP and the mixture treatments. A decrease in proline contents in comparison with the controls was reported earlier by Farahat et al (2012) during an investigation of exogenous applications of humic acid on seedlings of Khaya senegalensis.…”
Section: Proline Contentssupporting
confidence: 74%
“…Amending the soil with poultry manure significantly reduced counts of root galls, juveniles in soil, developmental stages, egg masses in root and final population of M. incognita,in addition, the usage of such materials did improve the plant growth. These result are in agreement with the findings of Kablan and Noe Farahat et al, 2008 (Karmani et al,( 2011) and Farahat et al( 2012). The nematicidal activity of poultry manure is mainly attributed to its contents of volatile fatty acids, phenols, amino acids, ammonia, nitrites and gasses which released during the decomposition of the manure; and to enhance soil populations of micro-organisms antagonistic to nematodes (Badra, et al, 1979;Mian, Rodrequez-Kabana, 1982;Lazarovits et al, 2001;Oka and Pivonia, 2002;and Farahat et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…This is due to TFP containing ammonia, phosphorus, and orthophosphate. Anhydrous and aqueous ammonia, urea, and other ammonium compounds have all been employed directly to control nematodes, therefore ammonia plays a significant part in this process (Farahat et al, 2012). These findings agree with those of Ferial et al (2011) who reported that phospho-fertilizer was most successful in lowering egg mass production, root galling, and egg hatching and survival of J2.…”
Section: Discussionsupporting
confidence: 89%